Analisis Hukuman Disiplin Pelajar dalam Perspektif Sosiologi Hukum - Susanto, Joko; Zen, Muhammad Alfin Aufillah; Irawan, Irawan; Effendi, Sasetya Bayu; Rahma, Dhiny Ligia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to investigate the implications of disciplinary punishment against students from the point of view of legal sociology. The research method used in this study is qualitative descriptive analysis by utilizing in-depth interviews with students, legal practitioners, and educators (teachers), then document analysis is carried out as a data collection technique. The results of the analysis show that disciplinary punishment against students has a complex impact in shaping student identity and behavior in the educational environment, thus requiring appropriate handling in terms of providing disciplinary punishment for students, for this article it is possible to find out the right solution in terms of handling disciplinary punishment for students. From the point of view of legal sociology, disciplinary punishment not only functions as a means of social control, but also as a means of reproduction of power and norms that apply in society. Disciplinary punishment can affect the relationship between students and teachers and its impact on the learning process and the psychological well-being of students. Disciplinary punishment against students is an integral part of the education system which has complex implications in shaping student behavior and identity